1999
DOI: 10.1111/j.1473-4192.1999.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of English pronunciation: learners' views

Abstract: This paper aims at describing English learners' views on the acquisition of the phonetic component of English by focusing on their awareness of the difficulty and importance of English pronunciation as well as their beliefs about influential factors in the acquisition of pronunciation and their attitudes towards English accents. It also aims at examining the differences in phonetic awareness, beliefs and attitudes between learners of English with different first languages (Basque and Spanish). All the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…The results of the study further confirmed Elliot's (1995) findings, where positive attitude was found to be the main variable in relation to language pronunciation, implying that students who were more concerned about their pronunciation, had more positive attitude towards target language and; therefore, were more successful in imitating correct pronunciation. The same finding was also observed in Cenoz and Garcia Lecumberri (1999) who stated that the positive attitude towards a target language and its culture, leads the person to choose the pronunciation with which they are identified for the second language. Similar results were also reported by Moyer (2007), who confirmed that language attitudes specifically towards the target language are significant for acquiring native like accent, and that positive orientations are important for attaining authenticity in accent.…”
Section: Research Question 3: Testing the Correlation Between Attitudsupporting
confidence: 64%
See 1 more Smart Citation
“…The results of the study further confirmed Elliot's (1995) findings, where positive attitude was found to be the main variable in relation to language pronunciation, implying that students who were more concerned about their pronunciation, had more positive attitude towards target language and; therefore, were more successful in imitating correct pronunciation. The same finding was also observed in Cenoz and Garcia Lecumberri (1999) who stated that the positive attitude towards a target language and its culture, leads the person to choose the pronunciation with which they are identified for the second language. Similar results were also reported by Moyer (2007), who confirmed that language attitudes specifically towards the target language are significant for acquiring native like accent, and that positive orientations are important for attaining authenticity in accent.…”
Section: Research Question 3: Testing the Correlation Between Attitudsupporting
confidence: 64%
“…As Cenoz and Garcia Lecumberri (1999) pointed out, in many cases, speakers tend to use the pronunciation they value as more positive, or try to choose the pronunciation with which they are identified for both their first and second languages. This point is related to the fact that attitude can be both culturally directed and language directed.…”
Section: Gender and Learning Suprasegmental Featuresmentioning
confidence: 99%
“… attitudes to pronunciation in EFL 1 (Porter and Garvin 1989);  attitudes to foreign accent or native-likeness in the L2; pronunciation selfevaluation (Hammond 1990);  the importance of 'good pronunciation' (Kenworthy 1990);  phonology in teacher training courses (Bradford and Kenworthy 1991);  factors affecting pronunciation learning (Edwards 1992 as cited in Barrera Pardo 2004);  knowledge of English pronunciation, motivation and self-awareness (CelceMurcia et al 1996);  the content of phonology courses in the USA (Murphy 1997);  motivation in pronunciation (Dalton and Smit 1997);  students' awareness of the difficulty and importance of English pronunciation; influential factors in the acquisition of pronunciation; attitudes towards English accents (Cenoz and Garcia-Lecumberri 1999);  teaching intonation among EFL practitioners (Roads, 1999);  proclaimed and perceived wants and needs among Spanish teachers of English (Walker 1999);  pronunciation learning styles (Basso 2000);  the effectiveness of teaching pronunciation to Malaysian TESL students (Rajadurai 2001  international students' attitudes towards English pronunciation and the comparison of Euro-English with the Lingua Franca Core (Bryła 2006);  students' evaluation of learner corpora in L2 prosody research and teaching (Gut 2007);  perception of foreign accent by native and non-native speakers (Vishnevskaya 2008);  personality traits (extroversion, empathy etc.) and pronunciation talent in L2 acquisition (Hu and Reiterer 2009);  musicality and the phonetic language aptitude (Nardo and Reiterer 2010);  pronunciation preferences for phonological variation among linguistically trained and untrained respondents (Benrabah 2010);  native and non-native perception of foreign-accented speech (Nowacka 2010);  students' attitude toward pronunciation: the perceived utility of pronunciation, level of confidence and interest in pronunciation, teachers' views and practices with regard to pronunciation instruction (Yeou 2010);  English pronunciation teaching practices in European countries/survey (Henderson, in press; Henderson and Frost et al in press);  pronunciation identity constructions of learners and speakers among Croatian students (Josipović Smojver and Stanojević, in press);  the phonetic needs of French EFL students (Nasser-Eddine, 2011);  students' metacognitive awareness; pronunciation learning strategies (Murphy, in press);...…”
Section: Introduction: the Outline Of Questionnaire-based Studiesmentioning
confidence: 99%
“…It has been concluded (Stephen, 1985) that the learners' anxiety, nervousness, lack of motivation, boredom and negative attitude could block incoming messages from reaching the language acquisition device (LAD) (as cited in Oller, 1988). Cenoz and Lecumberri(1999) contended that "the phonetic component of linguistic communication is immediately observable..., and it is in most cases the most salient characteristic of non-native speakers". Hence pronunciation is the most important and difficult part that non-native English learners have to face.…”
Section: Learning Anxiety and Lack Of Self-confidence In English Speamentioning
confidence: 99%